Greater visibility of Gaceta Técnica journal (Gaceta Técnica, 2020)
During the year 2019 the scientific publication Gaceta Técnica of Civil Engineering has been accepted by AmeliCA; which also promoted being coupled with the Declaration of San Francisco DORA and Aura, a platform through which AmeliCA reflects the situation of the journals with regard to the scientific openness and exploitation rights of the publications. Similarly, it was accepted in Redalyc, which is a recognized evaluation system for the indexation of open access journals, and from which AmeliCA was born in conjunction with other organizations. These achievements promote greater visibility of the magazine through the Web
Keywords: scientific visibility; Gaceta Técnica journal; AmeliCA; Redalyc